2003
DOI: 10.1590/s0102-311x2003000200022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de deficiência visual de perto e fatores associados: um estudo de base populacional

Abstract: The objective of this article was to estimate the prevalence of presbyopia in adults ≥ 30years and explore associated characteristics such as demographic, socioeconomic, and individual variables. A cross-sectional, population-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 12 publications
1
10
0
6
Order By: Relevance
“…In another review, from low-and middle-income countries, Patel and West [1] found that more than half of adults over the age of 30 have presbyopia. Duarte et al, in Brazil estimated the prevalence of presbyopia in 3,000 adults of 30 years and older at 54.7 percent [22]. In southern India, Nirmalan et al, found a prevalence of 55 percent in subjects aged 30 years and older [23].…”
Section: Discussionmentioning
confidence: 99%
“…In another review, from low-and middle-income countries, Patel and West [1] found that more than half of adults over the age of 30 have presbyopia. Duarte et al, in Brazil estimated the prevalence of presbyopia in 3,000 adults of 30 years and older at 54.7 percent [22]. In southern India, Nirmalan et al, found a prevalence of 55 percent in subjects aged 30 years and older [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the condition is related to epidemiological data such as age, sex, and social condition. This is because complaints of difficulties reading due to presbyopia depend on a person's educational or working needs as well as access to ophthalmic care (5,10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…However, some factors seem to influence the choice of therapy, such as age, sex, and social characteristics (5,6) .…”
mentioning
confidence: 99%
“…Isso é reforçado pela consistência, com a literatura, das prevalências de diabetes melito, toxoplasmose, glaucoma, catarata e uso de correção, tanto na população geral, quanto nos de 50 anos ou mais 1,20,21,22,23,24,25,26,27,28 . No caso da hipertensão arterial sistêmica, o presente estudo encontrou prevalência maior do que a encontrada por outro estudo realizado na mesma cidade.…”
Section: Variávelunclassified